ANALISIS EFISIENSI BIAYA PRODUKSI KATERING PADA USAHA RUMAH MAKAN TERAS (JURNAL ULET (Utility, Earning and Tax), 2024)
The purpose of this study was to determine the amount of production costs in catering production and to make production cost efficiency at Rumah Makan Teras in order to achieve the desired profit. This research is descriptive research.  The data used is primary data collected through observation, interviews and documentation, and analyzed using target costing. The results of this study indicate that, the cost of goods produced for fresh chicken products produced at Rumah Makan Teras is Rp. 31,642,- and for fresh fish products Rp. 31,403,-.  From the calculation of the cost of goods produced, the company is only able to generate a gross profit of 42% of the product selling price of Rp. 45,000 per serving, from this it has not reached the desired 50% gross profit, so it is necessary to make efficiency by applying target costing.  The efficiency of catering production costs at Rumah Makan Teras with the application of target costing can be carried out on the production cost components, namely the raw material component and factory overhead costs.  The component of raw material costs that can be streamlined is that the Cap Mawar brand rice is replaced with Pandan Sulawesi stamp rice with a savings of 9% and the Sania stamp cooking oil is replaced with Our Oil stamp cooking oil with a savings of 26% then for the factory overhead component can replace gas fuel by only using kerosene fuel, resulting in a savings of 35%. With the right efficiency steps, the Rumah Makan Teras business is able to achieve the desired profit of 50%.